Teaching L2 writing through the use of Systemic Functional Linguistics (SFL) - Setyo Prasiyanto Cahyono (Indonesian JELT, 2018)
This study aims to describe the implementation of systemic functional linguistics (SFL) of the textual grammar of message (or textual meaning) to enhance students’ critical response to the text they created. For EFL learners, transferring their ideas into writing is already a difficult task and that to give a response to the text they read or write critically is even more challenging. This study intends to approach the teaching of writing by adopting Halliday’s idea of textual meaning and Systemic Functional Linguistics (SFL). The students were introduced to samples of hortatory texts and trained to analyze the thematic patterns and grammatical cohesive devices. It is hoped that by training them to understand textual grammar (including thematic progression and cohesion), students (as readers and writers) are able to build their critical thinking skill and evaluate their own works. After the training, students were assigned to produce a hortatory text and to do self-editing activity. The data of this study were the twenty students’ hortatory texts which was analyzed using a framework of textual meaning proposed by Butt (2000). The analysis of the students texts show that most students were able to self-edit their own writings and edit their peer’s writing using thematic progression and cohesive devices. Students adopted skills of using both strategies in creating cohesiveness in their writing. In addition, students also produced critical response to the topic given through its theme and thematic displayed in the text analysis.